Belajar Sambil Bermain: Cara Sekolah Mendukung Motorik Kasar Anak Usia Dini - Andini, Shifa Jasyira; Farica, Meshcah Claula; Asmawulan, Tri (Early Childhood Research Journal (ECRJ), 2024)
Digital learning media, one example of the results of the rapid development of digital technology that has penetrated into the world of education including the stimulation of early childhood cognitive development. The aim of this article are discusses the utilization of digital educational media as a tool to stimulate cognitive optimally and effectively. Through a literature study approach, this article reviews recent literature to emphasize the role of digital media, such as Augmented Reality (AR), Virtual Reality (VR), zoom, digital flashcards, and learning applications and educational games, in improving early childhood cognitive development. This research uses the library research approach method or literature study. The result of these article is media not only increase learning motivation, but also help children develop critical thinking skills, creativity, and memory. Although this media offers many benefits, implementing this digital educational media must also face various challenges, such as infrastructure gaps, lack of digital literacy, resistance to change, and the quality of content that is not in accordance with the existing curriculum. This article also emphasizes the importance of careful planning, strong support from parents and teachers, and good management to optimize the benefits of digital learning media for early childhood development.